INOVASI 4.0 DALAM PEMBELAJARAN AKUNTANSI PADA SISWA/I SMK KARYA NASIONAL, KAB. KUNINGAN JAWA BARAT - Rosedi; Mohammad Sigit Adi Nugraha; Dedy Suryadi; Efrinal; Enggun Gunawan (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to determine innovation 4.0 in accounting learning for students at SMK Karya Nasional, Kab. Kuningan West Java. The digital era is a time where everyone can communicate with each other very closely, even though they are far apart. We can find out certain information very quickly, even in real time. Globalization is a process of international integration that occurs as a result of exchange of world views, products, ideas and other cultural aspects caused by the development of telecommunications, transportation and internet infrastructure. The result of the industrial revolution era 4.0 were also marked by the development of the internet and digital technology as well as the emergence of supercomputers and artificial intelligence. The education needed to enter the era of the industrial revolution 4.0 is learning that empowers students to be able to think critically, creatively, innovatively, collaborate and have high self-confidence. Revision of current skills is highly recommended to ensure the profession’s relevance in industry 4.0. enabling future accounting graduates to be accepted in the labor market. Developing the skills of future accountants must be the main agenda in this era. Online and distance learning must be the rise of education 4.0